Impacts potentiels des câbles électriques sous-marins des projets d’énergies marines renouvelables sur les écosystèmes benthiques - Taormina, Bastien (Unversité de Bretagne Occidentale, 2019)
renewable energy projects, the aim of this PhD thesis was to better characterise the potential impacts of submarine power cables on coastal benthic ecosystems. The work specifically focused on the impacts associated with the operational phase. The major part of this work was dedicated to the reef effect created by these cables and their protective and stabilising structures on sessile epibenthic communities and mobile megafauna. This work was mainly based on underwater imagery, either video or photo collected in situ by divers. The challenge of working with underwater imagery has led me to optimise image analyses so as to effectively monitor benthic colonisation and to quantify artificial reef habitat provision to commercial species. In addition to this reef effect, colonising organisms are exposed to magnetic fields generated by the power cables. Thus, I designed an experimental study to assess the impact of realistic magnetic fields on the behaviour of juvenile European lobsters (Homarus gammarus). Finally, we explored the ecological impacts of excluding anthropogenic activity from the cables routes and potential benefits for benthic macrofauna. By coupling both in situ and ex situ approaches, my PhD research better characterises the environmental impacts associated with submarine power cables. These results will help to assess the ecological footprint of future power grid connections. Dans un contexte de développement rapide des projets d’énergies marines renouvelables, le but de cette thèse était d’améliorer les connaissances sur les impacts potentiels des câbles électriques sous-marins sur les écosystèmes benthiques côtiers. En se focalisant sur la phase de fonctionnement, ce travail était essentiellement dédié à la caractérisation de l’effet récif généré par ces câbles et leurs structures associées (protection, stabilisation) sur les communautés épibenthiques fixées et la mégafaune mobile. L’étude était principalement basée sur l’utilisation d’images sous-marines (photo et vidéo) prises in situ par des ...